Siva Mahadeva: Suatu Analisis Ikonografi di Jawa Masa Hindu-Buddha - Maulana, Ratnaesih (Makara Human Behavior Studies in Asia, 2002)
The iconographic analysis of the deities on the “height measurement” showed that the tala measurement of the Javanese statues are not so different from those of the Indian “tala measurement”, i.e. the uttama-dasa-tala. The similarity between the Javanese Siva Mahadeva’s iconometry and the Siva Mahadeva statues in India showed that the Siva Mahadeva statues in Java have the same role with the Indian Siva Mahadeva statues. Among the 43 general laksanas of Siva Mahadeva, the camara (fl ywisk) is the most important one (about 21,2644%). However, in India the camara is not always belonged to Siva Mahadeva, because we found some lower deities have the same laksana. This reality showed that the Indonesian silpin were not always followed strictly the Indian manual books. They created the statues a.o. the Siva Mahadeva statues according to local concept (the Kamanunggalan).